The Experiences of Parents of Children Undergoing Surgery for Congenital Heart Defects: A Holistic Model of Care - David Vainberg, Leeza; Vardi, Amir; Jacoby, Rebecca (Frontiers in Psychology, 2019)
The present article is based on a qualitative study focusing on parents of children born with congenital heart defects (CHD) and hospitalized in the children’s intensive care unit (ICU) post-surgery. Our aim was to explore parents’ subjective experiences as primary caregivers. Ten semi-structured interviews were conducted and analyzed using interpretative phenomenological analysis (IPA) according to the instructions of Smith and Osborn. Our analysis yielded eight categories which were grouped into four themes and two main superordinate themes: 1. dialectical tension between positive and negative experiences; and 2. fluctuations between the inner and the outer world. The two superordinate themes intersect such that parents report positive as well as negative experiences within both their inner and outer worlds. Based on our analysis, we found that the experience of having a child undergo surgery for a CHD can be regarded as a chaotic period characterized by uncertainty, confusion, and helplessness. It is therefore no surprise that many parents display negative psychological outcomes which extend beyond the period of hospitalization and may also affect their future parenting and coping. However, within this chaotic and stressful situation, parents had occasional supportive experiences which decreased their emotional distress and isolation and helped them throughout this difficult period. We thus conclude that the support offered to parents during the hospitalization period should be increased by trying to minimize their negative experiences and strengthen their inner coping abilities. These changes cannot be implemented without also addressing the needs of the medical staff in their role as caregivers. Therefore, we propose a holistic model of care which supports both parents as caregivers of children undergoing surgery for CHD and the medical staff involved in their care.